A biobank of patient-derived pediatric brain tumor models. (November 2018) - Brabetz, Sebastian; Leary, Sarah; Gröbner, Susanne; Nakamoto, Madison; Şeker-Cin, Huriye; Girard, Emily; Cole, Bonnie; Strand, Andrew; Bloom, Karina; Hovestadt, Volker; Mack, Norman; Pakiam, Fiona; et al.
Abstract Brain tumors are the leading cause of cancer-related death in children. Genomic studies have provided insights into molecular subgroups and oncogenic drivers of pediatric brain tumors that may lead to novel therapeutic strategies. To evaluate new treatments, better preclinical models adequately reflecting the biological heterogeneity are needed. Through the Children's Oncology Group ACNS02B3 study, we have generated and comprehensively characterized 30 patient-derived orthotopic xenograft models and seven cell lines representing 14 molecular subgroups of pediatric brain tumors. Patient-derived orthotopic xenograft models were found to be representative of the human tumors they were derived from in terms of histology, immunohistochemistry, gene expression, DNA methylation, copy number, and mutational profiles. In vivo drug sensitivity of targeted therapeutics was associated with distinct molecular tumor subgroups and specific genetic alterations. These models and their molecular characterization provide an unprecedented resource for the cancer community to study key oncogenic drivers and to evaluate novel treatment strategies. A resource of preclinical pediatric brain tumor models with detailed molecular characterization provides a platform for the community to test novel therapeutic approaches.